#TITLE_ALTERNATIVE# - LAKSONO (NIM 13203020), PUJO
Differential GPS correction with single differential method provides solution to increase the accuracy of a GPS receiver by reducing any natural and technical biases that occurs in GPS signal propagation. This method also deals with the difference in receiver specifications that implies on the accuracy rate of each GPS receiver class. This research compared the capabilities of class-A GPS receivers with class-B GPS receivers, then implemented DGPS correction method as a technique to increase the accuracy of class-B receiver so that it can meet that of class-A receiver. A class-A NovAtel SuperStar II-FlexPak was used as a reference station, while a class B Polstar PMB-688 was used as the corrected receiver. The specially designed software can process data that were acquired from class-A receiver in forms of satellite positions (Xs, Ys, Zs), reference station position (Xr, Yr, Zr), and pseudorange (Pr), while from the class-B receiver was only pseudorange (Pm) parameter. Parameters processing was done by differentiating range equations between two GPS receivers against the same satellite. The calculations resulted in position of the corrected unit with error rates reaching 1000 meters. This error was later reduced by filtration method, in which the sum of the satellite used in positioning should be equal or more than six. This is related with the Geometric Dilution of Precision (GDOP in short) of a positioning, in which the larger the area covered by the satellite constellation, the GDOP score will be smaller, and in turn the accuracy will be higher. This final project research has successfully proven that DGPS correction method with applying the filtration criteria resulted in the accuracy increase of class-B receiver up to 1-9 meters error range, which is the accuracy of a class-A GPS receiver.